2010
DOI: 10.1007/s00442-010-1641-1
|View full text |Cite
|
Sign up to set email alerts
|

Widespread seed limitation affects plant density but not population trajectory in the invasive plant Centaurea solstitialis

Abstract: In some plant populations, the availability of seeds strongly regulates recruitment. However, a scarcity of germination microsites, granivory or density-dependent mortality can reduce the number of plants that germinate or survive to flower. The relative strengths of these controls are unknown for most plant populations and for exotic invaders in particular. We conducted a seed addition experiment with a granivore exclusion treatment in a field setting to explore how these factors interact to regulate populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…By the mid 20th century, the species was rapidly expanding through California's Central Valley and Sierra Nevada foothill grasslands, and the current leading edge of this invasion lies above 4,000 m in elevation along the west side of the Sierra Nevada Mountains (Pitcairn, Schoenig, Yacoub, & Gendron, ). In the North American invasion, habitat quality is often linked to the climatic environment, with warmer and drier habitats frequently supporting the densest C. solstitialis populations (Pitcairn et al, ; Swope & Parker, ). During expansion, C. solstitialis has crossed climatic gradients that are largely independent in direction from the pathway of colonization (Figure ), allowing us to quantify the influence of both climatic environment and expansion history (time since founding) on estimates of N e across populations.…”
Section: Introductionmentioning
confidence: 99%
“…By the mid 20th century, the species was rapidly expanding through California's Central Valley and Sierra Nevada foothill grasslands, and the current leading edge of this invasion lies above 4,000 m in elevation along the west side of the Sierra Nevada Mountains (Pitcairn, Schoenig, Yacoub, & Gendron, ). In the North American invasion, habitat quality is often linked to the climatic environment, with warmer and drier habitats frequently supporting the densest C. solstitialis populations (Pitcairn et al, ; Swope & Parker, ). During expansion, C. solstitialis has crossed climatic gradients that are largely independent in direction from the pathway of colonization (Figure ), allowing us to quantify the influence of both climatic environment and expansion history (time since founding) on estimates of N e across populations.…”
Section: Introductionmentioning
confidence: 99%
“…Seed limitation influences recruitment of many native (Turnbull et al 2000, Clark et al 2007) and non-native species (Jongejans et al 2007, Swope and Parker 2010, Connolly et al 2014. Seed limitation can be the product of 1) a paucity of reproducing plants, 2) poor seed dispersal, 3) biotic agents that directly reduce seed number, 4) poor propagule viability, or 5) some combination thereof (Harper 1977, Seabloom et al 2003, Davis 2009).…”
Section: Seed Limitation Disturbance and Naturalizationsmentioning
confidence: 99%
“…This is somewhat unfortunate given that in our previous work we detected the strongest seedlimited recruitment and no microsite limitation at this site compared to the others (Swope and Parker 2010b). This is somewhat unfortunate given that in our previous work we detected the strongest seedlimited recruitment and no microsite limitation at this site compared to the others (Swope and Parker 2010b).…”
Section: Impact Vs Effective Controlmentioning
confidence: 56%
“…Elsewhere we have shown that recruitment at the Coast and the Interior will vary between being seed-limited and microsite-limited at spatial scales relevant to dispersal, which for this species is a matter of meters or less (Swope and Parker 2010b). But it can be difficult to predict how effectively agents will control populations of their target weed based on their impacts on individual plants.…”
Section: Impact Vs Effective Controlmentioning
confidence: 99%